UJI SENSIVITAS KOLONI BDB (Blood Disease Bacterium) TERHADAP PEMBERIAN BAHAN KIMIA SECARA IN VITRO - Asrul Asrul (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Blood disease bacterium (BDB) has highly damaged banana plants in Central Sulawesi causing banana fruit produced from such plants are no longer edible.  The study aimed at testing the sensitivity of various chemical substances such as cupravit, antibiotic agrimycin, plant pesticide and garlic extract at different in vitro consentrates as an effort of controlling BDB patogen.  The study was conducted at The Bacteriology Unit, The Laboratory of Plant Pest and Disease, Faculty of Agriculture, UNTAD.  The concentrates used for each substance were 50, 100, 250, 500 and 1.000 ppm, respectively. The results of the study indicated that cupravit has the ability of inhibiting the growth of colony BDB greater than agrimycin and garlic extract.  The ability of cupravit in suppressing the growth of BDB colony is at 250 ppm concentrate, while agrimycin and garlic extract at 500 ppm concentrate